Analisis Kebijakan Desentralisasi Sistem Pendidikan Nasional dan Dampaknya Terhadap Pendidikan Madrasah - Eka Sulistiawati; Devi Riska Juliani D; Yuspiani Yuspiani; Musdalifah Musdalifah (Institusi Agama Islam Negeri (IAIN) Bone, 2024)
This article aims to analyze the decentralization policy of the national education system and its impact on madrasah education. This research employs a qualitative method with a literature review approach. Data sources are obtained through a literature study relevant to the impact of implementing the decentralization policy of the national education system. The study addresses several issues, including: 1) the decentralization of the national education system; and 2) the impact of decentralization on madrasah education. Data collection techniques involve a systematic literature search related to education decentralization policy based on systematic inclusion and exclusion criteria, as well as data organization based on themes. Data analysis is conducted through reading and marking, thematic analysis, and synthesis. This research shows that the decentralization of the national education system aims to grant local governments the authority to manage and develop an education system that aligns with the needs, characteristics, and challenges of the local community. However, in its implementation, decentralization faces various challenges, particularly in the context of madrasah education. Madrasahs often experience budget, infrastructure, and resource gaps compared to public schools, which affect the quality of education in madrasahs.